Hemocoagulation Conditions Associated with Venom-Induced Consumption Coagulopathy due to Snakebite in Humans - Prasetiyanti, Rinta; Hernaningsih, Yetti (Folia Medica Indonesiana, 2024)
Highlights: 1. This review comprehensively highlighted aspects of hematologic abnormalities in snakebites, a topic that remains understudied globally. 2. This review contributes insights into the field of snakebite research and improves the management of snakebites by examining the diverse effects of different types of snakebites on hemocoagulation status. Abstract Snakebite remains an underreported health hazard worldwide. The most common effects of snakebite envenomation globally are hematological disorders, with venom-induced consumption coagulopathy (VICC) being the most prevalent and significant condition. This review aimed to explore the hematological aspects of snakebite, with a focus on snakebite-induced consumption coagulopathy. We conducted a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through a search across several databases, namely PubMed, ScienceDirect, and Google Scholar. The inclusion criteria for this review were studies on snakebite envenomation in humans with a discussion of relevant cases. Additionally, the included studies were conducted between 2010 and 2023 and published in the English language. Studies on animal models were excluded. We used the keywords “venom-induced consumption coagulopathy AND snake